2022
DOI: 10.3389/fpubh.2022.921413
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation using CBCT of the mandibular asymmetry and the compensation mechanism in a growing patient: A case report

Abstract: BackgroundThis case report aims to evaluate the development and the compensation mechanisms of the mandibular asymmetry in a growing male patient using cone beam computed tomography (CBCT). In this case, the menton deviated on the right, a sporadic condition, which may be the consequence of a disorder in the mandibular growth.Case presentationThe young male patient was treated with rapid palatal expander (RPE) and Fränkel functional regulator III (FR-3). The initial CBCT was acquired at the beginning of therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…This compromised muscular coordination may contribute to asymmetry in soft tissue thickness [ 43 ]. Evidence suggested that the early correction of these posterior crossbite through maxillary expansion had the potential to restore two-arch coordination and muscle function, facilitated by the spontaneous adaptive dentoalveolar compensation observed in the lower arch [ 49 ]. The re-centering of the menton point was attributed to this compensatory mechanism, whereby the contralateral hemi-mandibular demonstrated a greater growth rate compared to the deviated side, resulting in an observable improvement in soft-tissue symmetry in the lower face [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This compromised muscular coordination may contribute to asymmetry in soft tissue thickness [ 43 ]. Evidence suggested that the early correction of these posterior crossbite through maxillary expansion had the potential to restore two-arch coordination and muscle function, facilitated by the spontaneous adaptive dentoalveolar compensation observed in the lower arch [ 49 ]. The re-centering of the menton point was attributed to this compensatory mechanism, whereby the contralateral hemi-mandibular demonstrated a greater growth rate compared to the deviated side, resulting in an observable improvement in soft-tissue symmetry in the lower face [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the CBCT exams, the head of the patient was oriented in a natural head position (NHP). NHP is a morphological analysis used in orthodontics and described in the anthropological literature as a reproducible and physiological head posture in a tridimensional space [ 16 , 17 ]. To obtain the NHP, all the patients looked into their own eyes through a frontal mirror positioned at a distance of 1.5 m. The patients were sitting with the back perpendicular to the floor, and the head was stabilized with ear rods in the external auditory meatus [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…After acquiring the CBCT data in the Dolphin software, the head was additionally oriented according to the three reference planes on the front, right and left views [ 16 , 17 ]. The cephalometric measurements were correctly performed using the widgets present in the software [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thanks to their design, the dental-craniofacial and cervical-postural systems, as well as the neuromuscular system, alveoli, TMJs (temporomandibular joint system), soft tissues, salivary glands, and mandibular and maxillary bases, are all reflected in the functional activity of EAs [21,25,42,[49][50][51][52][53][54].…”
Section: Design Principles Of Easmentioning
confidence: 99%
“…As a result, the device itself does not control dental movement. This neutral zone in which they are positioned is created by the harmony between the muscles of the lips, tongue, and cheeks [21,25,28,37,42,[49][50][51][52][53][54][55].…”
Section: Design Principles Of Easmentioning
confidence: 99%